Inclusive Talent Development as A Key for Talent Management and Talent Retention to Achieve Sustainable Human Resource Management in Rural Bank Sharia Indonesia - Setiawati, Anindya Prastiwi; Mujanah, Siti; ., Sumiati (Journal of Ecohumanism, 2025)
The aim of this research is to analyze inclusive talent development as the main factor in talent management and retention in order to achieve sustainable human resources at rural bank sharia. This research uses a qualitative case study method with propositional outcomes as research results. Interviews and documentation studies were used to collect data. The research results show that inclusive talent development practices not only influence individual growth but also play an important role in retaining talent within the organization. Aspects such as talent identification, focus on technical and generic competencies, as well as retention strategies such as career paths, promotions and increasing compensation according to position level are included in inclusive talent development. This conclusion describes a strategic and holistic view of sustainable human resource management at rural bank sharia, where the focus on talent development creates a work environment that supports, inspires and retains talent for company sustainability and success in a long term.